Anisotropy in the electronic transport properties of Weyl semimetal WTe2 single crystals - Rajveer Jha; Shota Onishi; Ryuji Higashinaka; Tatsuma D. Matsuda; Raquel A. Ribeiro; Yuji Aoki (AIP Advances, 2018)
We measure the electrical resistivity ρ of type-II Weyl semimetal WTe2 using high-quality single crystals for the current I along the a and b crystallographic directions in rotating magnetic fields in the plane perpendicular to the current direction. In zero field, ρ exhibits huge anisotropy and the ratio ρb/ρa develops with decreasing temperature approaching ∼30 at T = 0. A low-T power-law behavior of ρ∝Tn with n = 2.7-2.9 may reflect the characteristic carrier scattering mechanism, probably associated with the strongly T-dependent mobilities, which lead to the sign change in the Hall resistivity. In the Kohler plot, the magnitude of the transverse magnetoresistance (MR) differs by more than two orders of magnitude depending on the I- and B-directions. It also shows clear deviation of MR from the B2 dependence for all the configurations. No singular directions (magic angles) appear in the rotating B measurements.